Strategic Information Systems and Inter- Organizational Systems - Meiryani,; Sudrajat, Jajat; Daud, Zaidi Mat; Lindawati, ASL (International Journal of Psychosocial Rehabilitation, 2020)
Management must have true and accurate and trustworthy information that reflects various measures of company performance. Without information the activities taken to use strategy control will be very subjective and only have a small chance to consistently improve company performance. Information systems and organizations as places for their application interact and influence one another. Information systems must be designed to be able to serve the needs of important groups in the organization and will be shaped by the structure, tasks, targets, culture, politics, and management of the organization.The information systems department is a formal unit within the organization that is responsible for the functioning of the organization's information system. Strategic information system is an information system that implements a competitive strategy that provides a competitive advantage for the company through internal efficiency and comparative efficiency so as to help the company provide significant performance gains and improve its long-term performance.Computer-based or manual, formal or informal strategic information systems can perform this function by providing information services needed by top management. Information is the main source of successful control strategies.